Diamonds are not just a scientist’s best friend - Oostdam, Ron (Dutch Journal of Applied Linguistics, 2024)
In this response to Diamond is a scientist’s best friend, Ron Oostdam argues that diamond open access is morally worth striving for, but may be difficult to achieve.